Government Management Analysis With a System Approach at the Office of Settlements and Infrastructure - Rismawati, Rismawati; Ningsih, Marsudi Lestari; Ulfiandi, Ihsan Zikri (CV. Civiliza Publishing, 2025)
This study aims to explain and describe how government management processes are seen from the analysis of the organizing system which consists of division of labor, departmentalization, authority distribution and coordination in achieving efficiency and effectiveness in the Office of Settlements and Infrastructure in the Jeneponto District. This study uses the desk riptif method with high quality . Data collection techniques used are literature studies and field studies in the form of observations, interviews and documentation. This research was conducted at the relevant government agencies, namely the Department of Settlements and Prasana Jeneponto Regency. Based on the results of the research , the division of labor is considered to be still less than the basic work Departemenisation has been carried out quite well in both individual and group assignments. Authority distribution is poorly implemented, coordination is still not carried out so that it cannot be efficiently and effectively integrated.